2020
DOI: 10.9734/ijtdh/2020/v41i1530355
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mass Drug Administration on Prevalence of Schistosomiasis in Eight Riverine Communities in the Asuogyaman District of the Eastern Region, Ghana

Abstract: Background: The incidence of schistosomiasis in Ghana and more specifically in the Asuogyaman District had become a noticeable record following the creation of the Akosombo Dam in the early 1960s. This has inevitably since placed an enormous burden on the health service delivery systems in the geographical area. Mass Drug Administration (MDA) of Praziquantel has been used worldwide as a preventive and treatment intervention measure for the disease, and the study area is no exception. The study, therefore, aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…These variations observed between intervention and control communities in follow-up when compared to those obtained in baseline mean that other district-specific organizational factors than those attributed to implementation of the study might have influenced the results. These high MDA coverage rates are similar to what other recent studies carried out in Philippines [27], Ghana [34], Cote d’Ivoire, Kenya, Mozambique, Niger and Tanzania [35, 36], Sierra Leone [37], Togo [38] and Zanzibar [39]. A spatiotemporal modelling review [40] have also reported that schistosomiasis prevalence in sub-Saharan Africa has decreased considerably, most likely explained by the scale-up of preventive chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…These variations observed between intervention and control communities in follow-up when compared to those obtained in baseline mean that other district-specific organizational factors than those attributed to implementation of the study might have influenced the results. These high MDA coverage rates are similar to what other recent studies carried out in Philippines [27], Ghana [34], Cote d’Ivoire, Kenya, Mozambique, Niger and Tanzania [35, 36], Sierra Leone [37], Togo [38] and Zanzibar [39]. A spatiotemporal modelling review [40] have also reported that schistosomiasis prevalence in sub-Saharan Africa has decreased considerably, most likely explained by the scale-up of preventive chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…These variations observed between intervention and control communities in follow-up when compared to those obtained in baseline mean that other district-speci c organizational factors than those attributed to implementation of the study might have in uenced the results. These high MDA coverage rates are similar to what other recent studies carried out in Philippines [27], Ghana [34], Cote d'Ivoire, Kenya, Mozambique, Niger and Tanzania [35,36], Sierra Leone [37], Togo [38] and Zanzibar [39]. A spatiotemporal modelling review [40] has also reported that schistosomiasis prevalence in sub-Saharan Africa has decreased considerably, most likely explained by the scaleup of preventive chemotherapy.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, a significant proportion of children in the study area are unlikely to have received the MDA treatment year in year out. Similar surveys in other parts of Ghana, have shown that average uptake of Praziquantel targeted at school age children (SAC) can go as low as 41% but varies to as high as 85% [ 16 ]. Therefore, others have argued for an expansion of the MDA for SAC to include adults, pre-school children and school-aged children who are out of school using community-based distribution, though this has been difficult to implement due to logistic challenges including inadequate supply of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Ghana has been implementing mass drug administration (MDA) campaigns for school age children (SAC) for schistosomiasis since 2008 [ 15 ]. Notwithstanding the paucity of data on a national evaluation of the program, previous assessments from various endemic communities across the countries show that the MDA for SAC had a significant impact on schistosome prevalence, particularly prevalence of S. haematobium, bringing prevalence rates down to <15% [ 16 ]. Notably, MDA for SAC with Praziquantel in the Asuogyaman District of Eastern Region of Ghana is reported to have contributed in reducing the prevalence of urinary schistosomiasis to about 10.4%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation